Answers

  • Brainly User
2016-06-14T09:39:23+08:00
1) (2t + - 1) (t + 5) becomes (2t - 1) (t + 5)  = 2t² + 9t - 5

Steps in multiplying binomials:
   a) Multiply the FIRST TERMS ⇒ (2t)(t) = 2t²   
   b) Multiply the OUTER TERMS ⇒ (2t) (5) = 10t
   c) Multiply the INNER TERMS ⇒ (-1) (t) = -1t
   d) Multiply the LAST TERMS ⇒ (-1)(5) = -5

Combine the like terms, if any:
   
2t² + 10t - 1t - 5 = 2t² + 9t - 5

2) (x + 4) (x + 4) = x² + 4x + 4x + 16
                           = x² + 8x + 16  (Perfect Square Trinomial)

3) (2r -5) (2r - 5) = 4r² - 10r - 10r + 25
                           = 4r² -10r + 25  (Perfect Square Trinomial)

4) (3 - 4m)2 = 6 - 8m  or  -8m + 6

Please do the rest as practice exercises.  

0